Gray matter abnormalities and memory impairment in left mesial temporal lobe epilepsy - Olejnik, Agnieszka; Bala, Aleksandra; Rejner, Weronika; Gottman-Narożna, Antonina; Rysz, Andrzej; Kopytek-Beuzen, Maja; Naumczyk, Patrycja; Kunert, Przemysław (Frontiers in Human Neuroscience, 2025)
ObjectivesMesial temporal lobe epilepsy (MTLE) is a common neurological disorder, with memory impairment being one of its typical symptoms. Most previous studies have focused on assessing declarative memory directly related to hippocampal functions, but emerging data suggest a decline in the efficiency of other types of memory as well. The aim of this study was to comprehensively assess various types of memory and analyze the relationship between memory performance and the volume of selected gray matter structures.MethodsIn total, 21 patients with left-MTLE and 28 age- and education-matched healthy individuals underwent neuropsychological assessment using the Wechsler Memory Scale IV (WMS-IV) to evaluate memory functioning. Magnetic resonance imaging was also conducted to assess gray matter volume and structure in all participants.ResultsCompared with healthy controls, patients with left-MTLE showed significantly reduced performance in short-term verbal and visual memory, long-term verbal and visual memory, and working memory. Volumetric analysis revealed differences in gray matter volume between groups, with some structures being smaller and others larger in the patient group. Numerous correlations were found between WMS-IV scores and the volume of specific brain regions. Significant associations were observed both ipsilateral and contralateral to the epileptic focus, involving regions such as the cerebellar cortex, cingulate gyrus, insula, thalamus, and pallidum.ConclusionThis study expands our understanding of the memory profile in patients with MTLE. Neuropsychological testing showed that patients performed worse than controls across all assessed memory domains. Additionally, the study identified a distinct pattern of neuronal abnormalities and brain–behavior correlations. These findings suggest that the extent of structural brain anomalies may be linked to the severity of memory impairment in MTLE, underscoring the complex relationship between neuroanatomy and cognitive function in this population.